Learning preference among Arabic language learners via mobile learning management system platform (mobile LMS) using i-Taleem - Sahrir, Muhammad Sabri; Zainuddin, Nurkhamimi; Nasir, Mohd Shahrizal (editor@ijcrls.com, 2016)
In the new era of digital technology especially in the use of mobile learning among youth learners such as mobile gadgets, smartphones, I-Pads and so on, the learners are also affected by the mobile revolution in their learning preference of various educational platforms. As such, the implementation of learning management system (LMS) in a universitythrough normal web-based platform should be exploring the potential use of mobile technology and gadgets in mobile learning platform. This paper aims to investigate the learners’ preference of using mobile devices in learning Arabic in IIUM in order to explore their inclination towards using mobile learning technologies in a learning institution. The respondents were selected from an undergraduate learners in two sections of a course who were learning computer applications theoretically and practically in Arabic language for the Bachelor of Revealed Knowledge (Arabic Language and Literature) in International Islamic University Malaysia (IIUM). The respondents have been using both platforms of web-based and mobile-based LMS of IIUM I-Taleem for an academic semester in 2015 before responding to this online survey of 5 Likert- scale and an open ended questionnaire. General results of this study revealed that the learners are enjoying learning by using mobile devices although the web- based platform is still available. The use of mobile LMS among learners is found to provide extra learning support, motivation and self-learning option. Among thesuggestions for improvement are improving the internet connection facility for student via Wifi and providing mobile devices for learners to use for better implementation of mobile I-Taleem in IIUM.